Islamic Ecofeminism and The Future of Social Justice: Pathways to Sustainable Community Development - Hani Sholihah; Nurhayati, Sri; Zaki Aulia Lukman; Gumpanat Boriboon (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2025)
This article explores the intersection of Islamic law (Sharīʿah), social equality, and ecofeminism as a holistic approach to a just and sustainable future. Drawing on Qur’anic principles and both classical and contemporary Islamic legal thought, the paper examines how Islamic law upholds ʿadl (justice), mīzān (balance), and the protection of vulnerable groups, including women and the environment. By engaging ecofeminist perspectives, it argues that Islamic ethical teachings align with ecological consciousness and gender justice, thereby offering a framework for addressing contemporary socio-environmental challenges. The paper is explicitly situated within Islamic ecofeminism and a maqāṣid al-sharīʿah orientation, incorporating fiqh al-bī’ah to delineate pathways to sustainable community development in Muslim societies. The article further examines how integrating ecofeminist insights can enrich Islamic legal discourse and catalyze transformative action through women’s empowerment and inclusive governance in mosques and pesantren, ensuring social equality while safeguarding natural resources for future generations. The study concludes by proposing a paradigm shift that positions Islamic law as a dynamic and responsive instrument for achieving social and ecological justice in the contemporary world. Overall, the contribution clarifies normative–practical linkages between Islamic ecofeminist ethics and community-level policy and practice.